Computer Infrastructure Facilities and Services at National Institutes of Technology Libraries in India - Srinivasa Rao, Y.; Choudhury, B.K. (DESIDOC Journal of Library & Information Technology, 2010)
Computer infrastructure plays a critical role in the academic system for meeting teaching, learning and research needs. Libraries are an integral part of academic system. Adequate infrastructure facilities support academic libraries share their resources and services in an effective way. National Institute of Technology, erstwhile regional engineering college, are prime institutions and benchmark for technical education in India in the field of engineering, science and technology. This paper discusses the computer infrastructure facilities available at National Institutes of Technology across India and current status of computer-based library services offered by these institutions. DOI: 10.14429/djlit.30.282